2018
DOI: 10.1111/jth.14236
|View full text |Cite
|
Sign up to set email alerts
|

The chaperone‐like sodium phenylbutyrate improves factor IX intracellular trafficking and activity impaired by the frequent p.R294Q mutation

Abstract: Background Missense mutations often impair protein folding and intracellular processing, which can be improved by small compounds with chaperone-like activity. However, little has been done in coagulopathies, where even modest increases of functional levels could have therapeutic implications. Objectives To rescue the expression of factor IX (FIX) variants affected by missense mutations associated with type I hemophilia B (HB) through chaperone-like compounds. Methods Expression studies of recombinant (r)FIX v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Plots of the green intensity values (PDI or Golgi) and the red intensity values (coagulation proteins) at the same locations allowed a visual demonstration of signal colocalization. Similar methodology has been previously demonstrated as a measure of intracellular protein co-localization 66 . This same analysis was used to show negative co-localized detection of intracellular FIX with VWF in both LSECs and HUVECs.…”
Section: Quantification Of Fvii Fix Fx and Prothrombin Released Inmentioning
confidence: 87%
“…Plots of the green intensity values (PDI or Golgi) and the red intensity values (coagulation proteins) at the same locations allowed a visual demonstration of signal colocalization. Similar methodology has been previously demonstrated as a measure of intracellular protein co-localization 66 . This same analysis was used to show negative co-localized detection of intracellular FIX with VWF in both LSECs and HUVECs.…”
Section: Quantification Of Fvii Fix Fx and Prothrombin Released Inmentioning
confidence: 87%
“…It was also tested in a short-term clinical trial as a therapeutic approach for cystic fibrosis in patients harbouring the ΔF508 variant of the cystic fibrosis transmembrane conductance regulator [26]. Interestingly, 4-PBA has been reported to increase the secretion of other coagulation factor variants such as FVIII-F309S [27], FIX-R294Q [17], and protein C-A267T [16]. Previously, it was demonstrated that 4-PBA could rescue various mutant proteins arrested in the ER allowing them to be expressed on the cell surface and to be functionally correct [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Chemical chaperones are small compounds that can stabilize misfolded proteins and improve the protein-folding capacity of cells and thereby increase protein secretion [13, 14]. Despite their therapeutic potential, only a few studies have been performed on their effect on mutated coagulation proteins [1517], and no studies have so far been performed on FVII. In the present study, we therefore examined the potential effects of chemical chaperones on trafficking and secretion of the FVII variant p.Q160R.…”
Section: Introductionmentioning
confidence: 99%
“…Nonsense and missense mutations, which overall represent the most frequent gene alterations arising from point mutations, may affect protein synthesis at translational or post-translational levels or both. In general, nonsense mutations may result in the production of potentially unstable truncated proteins with loss-of-function features, whereas missense mutations may exert pleiotropic effects on protein biosynthesis/processing and/or secretion/function as well as affect pre-mRNA splicing when falling into exonic sequences, as exemplified by the several variants characterized in the coagulation field [105,110,127,128,129,130].…”
Section: Rescue Of Coagulation Factor Expression By Translational mentioning
confidence: 99%
“…In the first model, cells expressing the A267T PC variant with defective intracellular transport [206] were treated with several compounds, but only Na-PBA resulted in a dose-dependent (up to ~3 fold) and significant increase in PC antigen levels [207]. In the second model, Na-PBA appreciably improved, in a dose-dependent manner, the intracellular trafficking and secretion of the most frequent FIX missense variant p.R294Q associated with proportionally low FIX activity and antigen levels [130]. In particular, secreted protein levels of the R294Q variant significantly increased (up to ~6 fold) upon treatment of stably-expressing cells with Na-PBA, a finding that was further confirmed at the intracellular level by the observation of improved trafficking to the Golgi compartment.…”
Section: Rescue Of Coagulation Factor Expression By Translational mentioning
confidence: 99%